2016
DOI: 10.13075/ijomeh.1896.00691
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental phthalate exposure on pregnancy duration and birth outcomes

Abstract: Objectives: The objective of this study was to evaluate the impact of phthalate exposure on pregnancy duration and birth outcomes based on the Polish Mother and Child Cohort (REPRO_PL). Material and Methods: Phthalate exposure was determined by measuring 11 phthalate metabolites (mono-ethyl phthalate (MEP), mono-iso-butyl phthalate (MiBP), mono-n-butyl phthalate (MnBP), 3OH-mono-n-butyl phthalate (OH-MnBP), mono-benzyl phthalate (MBzP), mono-(2-ethylhexyl) phthalate (MEHP), mono-(2-ethyl-5-hydroxyhexyl) phthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 45 publications
0
27
1
1
Order By: Relevance
“…In another study of 68 women from Michigan, Watkins and colleagues (2016) observed an inverse relationship between the sum of DBP metabolites (MBP, MHBP, MCPP) at delivery and gestational age [ 38 ]. Polanska and colleagues (2016) observed significant inverse associations between maternal MEP in the third trimester and gestational age from a prospective birth cohort in Poland ( N = 165) [ 36 ]. In a cohort of strictly African American and Dominican women in New York ( N = 331), Whyatt and colleagues (2009) found that shorter gestational duration was significantly associated with higher maternal urinary concentrations of MEHP, MEHHP, MEOHP, and MECPP in the third trimester [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study of 68 women from Michigan, Watkins and colleagues (2016) observed an inverse relationship between the sum of DBP metabolites (MBP, MHBP, MCPP) at delivery and gestational age [ 38 ]. Polanska and colleagues (2016) observed significant inverse associations between maternal MEP in the third trimester and gestational age from a prospective birth cohort in Poland ( N = 165) [ 36 ]. In a cohort of strictly African American and Dominican women in New York ( N = 331), Whyatt and colleagues (2009) found that shorter gestational duration was significantly associated with higher maternal urinary concentrations of MEHP, MEHHP, MEOHP, and MECPP in the third trimester [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…While in an Italian study, and association was found between MEHP and the shorter mean gestational age (8.4 days) alone (68). Aside from measuring phthalate metabolites in cord blood, most researches (69,84,85) focused on assessing phthalate exposure via maternal urine. After adjustment for possible confounders, a negative association between the pregnancy duration and maternal urinary MEP in the third trimester was observed in a prospective cohort from Poland (n = 165), which was of borderline significance (84).…”
Section: Prenatal Phthalate Exposure and Gestational Agementioning
confidence: 99%
“…Somewhat surprisingly, we found that phthalate polymers from drugs appear to have similar effects. Some studies have addressed the potential association between environmental phthalate exposure (assessed by biomarkers) and PTB or differences in gestational age 3,[25][26][27][28][29][30][31][32] . Studies that focus on gestational age are less conclusive, whereas studies that address the risk of PTB, support an association.…”
Section: Commentmentioning
confidence: 99%